Peranan Majelis Taklim dalam Pembinaan Keberagamaan bagi Ibu Rumah Tangga - Oksy Almaidah; Novia Nengsih (Jurnal Kawakib, 2021)
This study aims to determine and describe how the role of the taklim assembly in fostering religiosity in the aspect of worship for housewives; the role of the taklim assembly in fostering the religious reading of the Qur'an; the role of the taklim assembly in fostering religious diversity in the social aspect; and what are the supporting and inhibiting factors in religious development for housewives. The type of research used is qualitative research (field research), qualitative research methods are descriptive methods in the form of writing or words from people and observed behavior. Sources of data obtained from the congregation taklim assembly. To strengthen the research data obtained, the authors also took data through observation and documentation. All interview data were analyzed by collecting, reducing, presenting and ending with conclusion. The results of the study indicate that the role of the taklim assembly in religious development for housewives in various aspects, namely aspects of worship, the Koran, and social plays a very important role in broadcasting and developing Islam in society, especially for housewives